ChemInform Abstract: Titanocene(III) Chloride Mediated Radical‐Induced Opening of Monosubstituted Epoxy Acetates for the Synthesis of Primary Allylic Alcohols. Issue 49 (December 2015) - Chakraborty, P.; Mandal, S. K.; Roy, S. C.
Abstract: Primary allylic alcohols (II) are simply and efficiently synthesized from monosubstituted epoxy acetates (I) by title reaction via acetate elimination.